2020
DOI: 10.1007/s00477-020-01852-7
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of changes in the watershed partitioning level and optimization algorithm on runoff simulation: decomposition of uncertainties

Abstract: Hydrological modeling has provided key insights into the mechanisms of model state, such as the watershed partitioning level and optimization algorithm, and their impacts on the hydrological process, but the uncertainty of this impact is poorly understood. To this end, in this study, the effects of the watershed partitioning level and optimization algorithm for hydrological simulation uncertainty were assessed based on the semi-distributed TOPMODEL model, i.e., six watershed partitioning levels and three intel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Most such studies have focused on temperature and precipitation (Evin et al., 2019; Lehner et al., 2020; Zhou, Lu, et al., 2020), and they have found that model uncertainty dominates the uncertainty of temperature and precipitation projections, while the contribution of internal variability decreases with time, and the contribution of scenario uncertainty increases with time. The decomposition of uncertainty in projections of runoff changes based on the CMIP models has mostly not been explored; the sources of decomposition vary and mostly do not involve internal variability and scenario uncertainty (Finger et al., 2012; Zhou, Wang, et al., 2020; Zhou, Wang, Li, Chang, & Guo, 2021). Furthermore, these studies have focused mainly on the watershed scale—looking at, for example, the Alpine Rhine (Bosshard et al., 2013), the Swiss Alps (Finger et al., 2012), the Jialing River (Zhou, Wang, Li, Chang, & Guo, 2021), and 12 large‐scale river basins (Vetter et al., 2017)—while studies on the global scale are not yet available.…”
Section: Introductionmentioning
confidence: 99%
“…Most such studies have focused on temperature and precipitation (Evin et al., 2019; Lehner et al., 2020; Zhou, Lu, et al., 2020), and they have found that model uncertainty dominates the uncertainty of temperature and precipitation projections, while the contribution of internal variability decreases with time, and the contribution of scenario uncertainty increases with time. The decomposition of uncertainty in projections of runoff changes based on the CMIP models has mostly not been explored; the sources of decomposition vary and mostly do not involve internal variability and scenario uncertainty (Finger et al., 2012; Zhou, Wang, et al., 2020; Zhou, Wang, Li, Chang, & Guo, 2021). Furthermore, these studies have focused mainly on the watershed scale—looking at, for example, the Alpine Rhine (Bosshard et al., 2013), the Swiss Alps (Finger et al., 2012), the Jialing River (Zhou, Wang, Li, Chang, & Guo, 2021), and 12 large‐scale river basins (Vetter et al., 2017)—while studies on the global scale are not yet available.…”
Section: Introductionmentioning
confidence: 99%